A phase II trial of ruxolitinib in combination with azacytidine in myelodysplastic syndrome/myeloproliferative neoplasms. Issue 2 (27th November 2017) - Assi, Rita; Kantarjian, Hagop M.; Garcia‐Manero, Guillermo; Cortes, Jorge E.; Pemmaraju, Naveen; Wang, Xuemei; Nogueras‐Gonzalez, Graciela; Jabbour, Elias; Bose, Prithviraj; Kadia, Tapan; Dinardo, Courtney D.; Patel, Keyur; et al.
Abstract: Ruxolitinib and azacytidine target distinct disease manifestations of myelodysplastic syndrome/myeloproliferative neoplasms (MDS/MPNs). Patients with MDS/MPNs initially received ruxolitinib BID (doses based on platelets count), continuously in 28‐day cycles for the first 3 cycles. Azacytidine 25 mg/m 2 (Day 1‐5) intravenously or subcutaneously was recommended to be added to each cycle starting cycle 4 and could be increased to 75 mg/m 2 (Days 1‐5) for disease control. Azacytidine could be started earlier than cycle 4 and/or at higher dose in patients with rapidly proliferative disease or with elevated blasts. Thirty‐five patients were treated (MDS/MPN‐U, n =14; CMML, n =17; aCML, n =4), with a median follow‐up of 15.2 months (range, 1.0–41.5). All patients were evaluable by the 2015 international consortium proposal of response criteria for MDS/MPNs (ICP MDS/MPN) and 20 (57%) responded. Nine patients (45%) responded after the addition of azacytidine. A greater than 50% reduction in palpable splenomegaly at 24 weeks was noted in 9/14 (64%) patients. Responders more frequently were JAK2 ‐mutated ( P = .02) and had splenomegaly ( P = .03) compared to nonresponders. New onset grade 3/4 anemia and thrombocytopenia occurred in 18 (51%) and 19 (54%) patients, respectively, but required therapy discontinuation in only 1 (3%) patient. Patients with MDS/MPN‐U had better median survival compared to CMML and aCML (26.5 vs 15.1 vs 8 months; P = .034). The combination of ruxolitinib and azacytidine was well‐tolerated with an ICP MDS/MPN‐response rate of 57% in patients with MDS/MPNs. The survival benefit was most prominent in patients with MDS/MPN‐U.